2013
DOI: 10.1039/c3cc42570c
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrocatalyzed reduction of acetic and butyric acids via direct electron transfer using a mixed culture of sulfate-reducers drives electrosynthesis of alcohols and acetone

Abstract: Sulfate-reducing bacteria (SRB) developed biocathodes efficient for reduction of acetic and butyric acids to alcohols and acetone via direct electron transfer reaching current densities of 160-210 A m(-2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 32 publications
3
93
0
1
Order By: Relevance
“…However, the major research focus is currently directed at microbial bioelectrochemical systems [1]. Enzymatic electrocatalysis involving energy applications has remained more discrete.…”
Section: Introductionmentioning
confidence: 99%
“…However, the major research focus is currently directed at microbial bioelectrochemical systems [1]. Enzymatic electrocatalysis involving energy applications has remained more discrete.…”
Section: Introductionmentioning
confidence: 99%
“…In most MFCs the electrons that reach the cathode combine with protons (that diffuse from the anode through a separator) and with O2 (provided from air) producing water as the end product. The idea of using bacteria to generate electricity has been around for some time, but so far power production was very low and required the addition of exogenous mediators to shuttle electrons from the cell to the electrode surface [5]. For example, in the last 10 years the power density has increased by five orders of magnitude to 27 W· m −3 [6].…”
Section: Photosynthetic Microbial Electrochemical Cell (Pmec)mentioning
confidence: 99%
“…Although SRB was reported to play an important role in transferring electrons on the anode, some groups of SRB that could not form biofilm on the electrode may also reduce sulfate in the planktonic niche [42]. It has already been reported that SRB demonstrate functional dynamics, including electron transfer, sulfate reduction, and converting organic matters, such as acetic and butyric acids to alcohols and acetone via direct electron transfer [43][44][45]. In the present study, therefore, high-abundance groups (Desulfobulbus and Desulfovibrio) may perform both electron transfer on the electrode and sulfate reduction in the electrolyte, whereas low-abundance groups may focus primarily on transferring electrons in the electrode.…”
Section: Sulfate Reducing Bacteriamentioning
confidence: 99%